2019
DOI: 10.1002/app.48489
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the interactions between collagen and a naturally derived crosslinker, oxidized chitosan oligosaccharide

Abstract: Collagen has been widely applied to biomaterials. However, it must be chemically fixed before it can be used. The aim of this work is to study on the crosslinking effect of a naturally derived oxidized chitosan oligosaccharide (OCOS) on collagen type I. The physicochemical properties and biocompatibility of the crosslinked collagen (OCOS-Col) were evaluated. The FTIR spectroscopy showed that crosslinking via OCOS had no impact on the structural integrity of collagen. DSC and TG tests showed that the thermal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…They reported that dialdehyde cellulose did not have any observable impact on the cytotoxicity of hydrogels and all tested materials were nontoxic after 48 and 96 h of cell culture [ 67 ]. Following to Chen et al [ 68 ], membranes based on collagen, cross-linked with oxidized chitosan oligosaccharide, have a good biocompatibility. They evaluated toxicity of the materials by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide) assay with L929 fibroblast cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…They reported that dialdehyde cellulose did not have any observable impact on the cytotoxicity of hydrogels and all tested materials were nontoxic after 48 and 96 h of cell culture [ 67 ]. Following to Chen et al [ 68 ], membranes based on collagen, cross-linked with oxidized chitosan oligosaccharide, have a good biocompatibility. They evaluated toxicity of the materials by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide) assay with L929 fibroblast cells.…”
Section: Resultsmentioning
confidence: 99%
“…They evaluated toxicity of the materials by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide) assay with L929 fibroblast cells. It was noticed that higher amount than 2% of cross-linking agent, increased cytotoxicity effect of the material, however thanks to confocal microscopy they observed a little adverse effect on cell growth and proper proliferation of the cells was visible [ 68 ]. The fibroblast cells grow well with proper morphology on the surface of the membranes cross-linked with oxidized chitosan oligosaccharide [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, dialdehyde compounds derived from natural biomass with good biodegradability and low toxicity have attracted increasing attention. The thermal stability of collagen have been demonstrated to be improved by dialdehyde compounds such as oxidized glycogen, oxidized chitosan oligosaccharide, dialdehyde cellulose, oxidized sodium alginate and dialdehyde carboxymethyl cellulose (DCMC) [215][216][217][218]. A collagen cryogel was prepared by Tan et al [219] using dialdehyde carboxymethyl cellulose to crosslink collagen in solution at different DCMC/Col weight ratios of 0.0-0.2% with constant collagen concentration of 5 mg/ml.…”
Section: Other Crosslinkersmentioning
confidence: 99%